Arbuscular Mycorrhizal Fungi (AMF) Helps in Mitigating the Growth and Enzymatic Changes in Potato (Solanum tuberosum) Seedlings under Salinity Stress Conditions - Dad, Khaliq; Iftikhar, Sumiyya; Siddique, Faryal; Asad, Fakhra; Hasnain, Aleeza; Bint-e-Usman, Fatimah; Khaliq, Faizan; Nawaz, Muhammad (Indus Journal of Bioscience Research, 2025)
Salinity stress is a major problem that limits the growth and yield of crops worldwide. Arbuscular mycorrhizal fungi (AMF) are known to improve plant growth by enhancing nutrient uptake and stress tolerance. A pot experiment was conducted by using Funneliformis mosseae and salinity levels of 150 mM & 200 mM NaCl, arranged in a completely randomized block design manner in order to examine the potential of mycorrhizal fungi in mitigating the adverse impacts of salinity. The results showed that inoculation markedly enhanced growth parameters i.e. root length increased by 88.25%, shoot length by 220.1%, root fresh weight by 98.7%, and shoot fresh weight by 77.2% as compared to control. Chlorophyll contents were also affected under salt stress by 23.2% and 9.2%, while found improved with AMF. Superoxide Dismutase (SOD) activity was observed increased by 28.9%, Peroxidase (POD) activity increased to 36.4%, and Ascorbate Peroxidase (APX) activity by 56.25% as compared to the control. In the presence of 200 mM NaCl, AMF-treated plants exhibited SOD activity at 8.5 µmol/g fw and POD activity at 1.35 µmol/g fw, reflecting improved oxidative stress tolerance. Catalase (CAT) activity was enhanced by 50% in AMF-treated plants under salt stress. These results demonstrated that AMF played a crucial role in enhancing antioxidant defense mechanisms and mitigating oxidative damage in potato plants under salt stress conditions. So it can be concluded that AMF inoculation possesses potential in mitigating the salt stress and induce changes in growth and physiological attributes of plants.